Wine industry: an empirical research on consumers- knowledge and behaviour regarding Portuguese wine - Manfredi, Francisca Laura (2022)
The aim of this research is to understand consumers’ perceptionand knowledgeof Portuguesewinein relation with upcoming trends in the wine industry. This industry represents an economic trampoline for Portugal, as it is an increasingly attractive market that is now undergoing changes, as is the hospitality industry as a whole. A survey sample of data has been examined for this research, in order to understand consumer behavior and perception regarding Portuguese wine. Disinformation and lack of knowledge on this topic, in foreign countries, gives space to new trends, such as wine tourism, an effective marketing tool.